Endometritis risk factors after arterial embolisation for postpartum haemorrhage - Tsukasa Yoshida; Takeshi Nagao; Kuniyoshi Hayashi; Michiko Yamanaka (Taylor & Francis Group, 2023)
Various complications of arterial embolisation (AE) for postpartum haemorrhage (PPH) are reported. Endometritis (EM) frequently causes abscesses, increasing hysterectomy risk. However, risk factors for EM after AE for PPH are unclear. We explored these risk factors. We included patients who underwent AE for PPH in our hospital from 2005 to 2020 and compared those who did (EM group) and did not develop EM after AE (non-EM group) in a case-control study. Twenty patients met the study criteria; eight patients (40%) had EM. There were no differences in risk factors between groups involved in infection, such as premature rupture of membranes. However, the contrast medium extravasation rate on computed tomography scans before the AE procedure was significantly higher in the EM group (p=.019) compared to the non-EM group. The greatest EM risk factor was contrast medium extravasation before AE for PPH, determined by classification and regression tree modelling (relative risk: 4.5).Impact Statement What is already known on this subject? Reportedly, the clinical success rate of arterial embolisation (AE) for critical haemorrhage in obstetrics is high, around 90%. However, information regarding AE complications is limited. Endometritis is one of these complications, which not only causes prolonged hospitalisation but may also require further treatment, such as hysterectomy. However, the incidence rate and risk factors for EM remain unknown. What do the results of this study add? In this study, 40.0% of patients developed EM after AE for PPH. Extravasation of contrast medium was the top risk factor (relative risk: 4.5 compared to those without EM, p=.019). The second-leading risk factor was a bleeding volume greater than 2500 mL (relative risk: 4.5 compared to those without EM, p=.019). What are the implications of these findings for future clinical practice and/or future research? We created an EM prediction model using extravasation and a bleeding volume greater than 2500 mL. The model was 87.5% sensitive and 66.7% specific. This prediction model allows for the early detection and treatment of EM by recognising high-risk patients and providing intensive postpartum management.